Modeling, tuning, and validating of exciter and governor in combined-cycle power plants: a practical case study - Baswaimi, Saleh; Verayiah, Renuga; Xu, Tan Yi; Panneerchelvan, Nagaraja Rupan; Abidin, Aidil Azwin Zainul; Marsadek, Marayati; Ramasamy, Agileswari K.; Abidin, Izham Zainal; Jaafar, W. Mohd Suhaimi Wan (Institute of Advanced Engineering and Science, 2025)
Exciter and governor systems are critical to regulating power output and maintaining stability in power systems. Despite their significance, there is a lack of practical methodologies that leverage real power plant data for modeling, tuning, and validation. This research paper seeks to fill this gap by presenting a methodology that utilizes a transfer function and control algorithms for tuning and validation. The proposed approach is demonstrated through a case study of a practical combined-cycle power plant in Malaysia. The control algorithm's effectiveness is verified through MATLAB and Simulink simulations. Post-tuning assessments confirm the method’s ability to accurately determine tunable control parameter settings, meeting system requirements while ensuring grid stability and reliability. This versatile approach can be applied to various power plant configurations, making it a valuable tool for optimizing operations.